ENVIRONMENTAL, SOCIAL, GOVERNANCE (ESG), CARBON EMISSIONS, AND GREEN INVESTMENT: DETERMINANTS OF FIRM VALUE IN THE ERA OF SUSTAINABILITY - Lintang Shafa Zahra Zahra; Aisha Hanif (International Journal of Economic Integration and Regional Competitiveness, 2025)
Objective: This study investigates the influence of Environmental, Social, and Governance (ESG) scores, carbon emission intensity, and green investment on firm value in response to increasing climate change pressures and the growing importance of sustainability in investment decisions. Method: A quantitative approach was employed using purposive sampling on companies listed on the Indonesia Stock Exchange that reported ESG values from 2021 to 2024, with data analyzed through multiple linear regression. Results: The findings indicate that ESG scores significantly enhance firm value, demonstrating the importance of effective environmental, social, and governance management. Carbon emission intensity also affects firm value, suggesting that emission levels serve as indicators of environmental performance and sustainability risk perceptions. Furthermore, green investment shows a measurable impact on firm value, emphasizing the need for strategic allocation of sustainability-related capital to balance both short- and long-term financial outcomes. Novelty: This study provides empirical evidence from the Indonesian market on the combined effects of ESG performance, carbon emission intensity, and green investment on firm value, offering new insights into how sustainability dimensions shape corporate valuation in emerging economies